The Impact of the Retirement Slowdown on the US Youth Labor Market - Mohnen, Paul (Journal of Labor Economics, 2025)
Exploiting cross–commuting zone differences in age composition among the old, this paper estimates the impact of retirements on youth labor market outcomes over the period 1980–2017. In commuting zones where fewer workers retire because of the initial age structure, there is no evidence of significant effects on youth employment, but the share of younger workers in high-skill jobs declines, while the share of younger workers in low-skill jobs rises. Fewer retirements also leads to declining youth wages and lower job mobility. This suggests that the retirement slowdown in recent decades has contributed to deteriorating early-career outcomes.